Easy Money, Easy Spending: Evidence from Commodity Export Windfalls - Rabah Arezki; Hieu Nguyen; Rick van der Ploeg (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2025)
When wealth or income rises suddenly, the propensity for that "easy money" to be directed towards unproductive use, "easy spending", may rise. The cross-country relationship between conspicuous consumption and revenue windfalls is explored by estimating the response of demand for imports of luxury goods resulting from country-specific and plausibly exogenous variation in commodity export prices. The response of imports of luxury goods following a commodity export windfall is found to be bigger than that for non-luxury imports while there is substantial heterogeneity in the magnitude of the response between different categories of luxury import goods. The results also point to a significant increase in tourism from countries experiencing commodity export windfalls to the main luxury shopping destinations abroad. Countries that have higher inequality, weaker control of corruption or less democracy have significantly higher luxury import response following a commodity export windfall. This (luxury) import channel of the resource curse stems from the link between easy money and easy spending when weak mechanisms for resource allocation are in place.
Keywords: JEL-Codes; 330; conspicuous consumption; commodity prices; institutions; resource curse